The Effect of Fertilization on Growth Response of Porang (Amorphophallus oncophyllus Prain) in Dipterocarp Forests, East Kalimantan Indonesia - Kasransyah, Kasransyah; Marjenah, Marjenah; Rujehan, Rujehan; Karyati, Karyati; Ruslim, Yosep; Matius, Paulus; Syahrinudin, Syahrinudin; Soetioso, Rusdi; Wasli, Mohd Effendi; Toma, Takeshi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
The use of forest land under dipterocarp for agroforestry is hindered by the problem of low fertility, necessitating the application of fertilization from organic materials, such as manure, compost, or biochar. These materials provide essential nutrients, including nitrogen, carbon, phosphorus, and potassium, increase cation exchange capacity (CEC), neutralize the pH, and enhance soil texture and water retention. This study aims to determine the effect of fertilization on the growth of Porang in the dipterocarp forest in PT Utama Damai Indah Timber East Kalimantan. It was conducted from August 2021 to July 2022. A completely randomized design (CRD) was used with three replications at five treatment levels: manure 1000 g/plant (P1), compost 1000 g/plant (P2), biochar + manure 1000 g/plant (P3), biochar + compost 1000 g/plant (P4), and control without fertilization (P0). Data analysis was performed using ANOVA, followed by the Duncan test at a 10% level. The results showed that applying organic fertilizer enhanced soil's physical and chemical properties significantly. The combination of biochar and manure, at 1000 g/plant, proved to be the most effective treatment for increasing the height and yield of Porang compared to the control and other treatments.